Kata Majemuk yang Ditemukan di dalam Video Tati "JLo’s Makeup Artist Does My Makeup" - Ramadhani, Devi (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 31 No 1 (2024): Maret, 2024)
This study entitled Compound Words Found in Tati’s Video “JLo’s Makeup Artist Does My Makeup”. This study aimed to identify and classify the types of compound words found in Tati’s video “JLo’s Makeup Artist Does My Makeup” and to analyze the meaning of the compound words conveyed in Tati’s video “JLo’s Makeup Artist Does My Makeup”. The data was taken from Tati’s videos on YouTube titled “JLo’s Makeup Artist Does My Makeup”. The method used in data collection was documentation with note-taking techniques. The qualitative method was used in analyzing the data that had been collected. The data analysis was presented using formal and informal methods. The results of this study showed that 45 compound words were found in all the conversations in Tati’s video “JLo’s Makeup Artist Does My Makeup”. Based on the two problems of the study, there were three types of compound words; 28 compound nouns, five compound adjectives, and 12 compound verbs. In analyzing the meaning of the compound words, it had been found two types; 17 transparent meanings and 28 opaque meanings. Keywords:   compound words, meaning, video